Redescription of Liopropoma aragai (Teleostei: Serranidae), with two new confirmed records of species of Liopropoma from Taiwan - Koeda, Keita; Senou, Hiroshi; Chang, Chih-Wei; Ho, Hsuan-Ching (Zootaxa, 2019)
Liopropoma aragai Randall & Taylor 1988 is redescribed based on the holotype and non-type specimens from Japan and Taiwan. Diagnostic characters of the species and the status of Taiwanese specimens previously referred to L. aragai are reassessed. Liopropoma lemniscatum Randall & Taylor 1988, previously recorded only from the Pacific coast of Japan and the Ryukyu Archipelago, and L. lunulatum (Guichenot 1863), previously known from Okinawa Island (Japan), Guam, Réunion, Rarotonga and Tahiti, are redescribed, both being confirmed for the first time by voucher specimens from Taiwanese waters. A detailed description of each species and a key to Taiwan Liopropoma Gill 1861 is provided.